Effect of ethrel and nitrogen on nitrate reductase activity, photosynthesis, biomass and yield of mustard (Brassica juncea L. Czern and Coss) - Ashraf, K.A. Bhat, R. Rashid, A. Hassan, N. Ahmad, S. Akhtar, J.A. Bhat, M. Habib, N.A. Lone, M.R. Mir, M.A. Bhatï€ª, H. (Recent Research in Science and Technology, 2010)
Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â The plants of mustard (Brassica juncea L. Czern and Coss; cultivar Alankar) were treated with 200 Ã‚ÂµL/L ethrel (2-chloro ethyl phosphonic acid) at flowering stage (60 d after sowing) along with basal application of nitrogen 40, 60, and 80 kg N ha-1. Effect of ethrel and nitrogen on leaf area index (LAI), net photosynthetic rate (PN), nitrate reductase (NR) activity and plant dry mass were recorded at 80 and 100 d after sowing. At harvest pods plant-1, 1000 seed mass and seed yield were recorded. Ethrel 200 Ã‚ÂµL/L x 80 kg N ha-1 treatment enhanced all the characteristics studied during the experiment.